2002
DOI: 10.1001/archinte.162.19.2217
|View full text |Cite
|
Sign up to set email alerts
|

Undertreatment of Osteoporosis in Men With Hip Fracture

Abstract: The burden of hip fracture is illustrated by the high incidence of postfracture disability and the high mortality rate in both men and women. Nevertheless, few men receive antiresorptive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
205
0
7

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(222 citation statements)
references
References 31 publications
7
205
0
7
Order By: Relevance
“…(21) For example, men who have sustained an obvious fragility fracture (and who have osteoporosis on clinical grounds) are rarely evaluated for osteoporosis, and this cannot be corrected simply by using a different reference population. (21,22) When FRAX or other absolute fracture assessment systems are used in men, it is essential to clearly indicate the BMD normalization procedure to be used. To avoid confusion, the latest Web-based version of the FRAX tool now allows for absolute BMD to be entered directly (with equipment manufacture designation).…”
Section: Discussionmentioning
confidence: 99%
“…(21) For example, men who have sustained an obvious fragility fracture (and who have osteoporosis on clinical grounds) are rarely evaluated for osteoporosis, and this cannot be corrected simply by using a different reference population. (21,22) When FRAX or other absolute fracture assessment systems are used in men, it is essential to clearly indicate the BMD normalization procedure to be used. To avoid confusion, the latest Web-based version of the FRAX tool now allows for absolute BMD to be entered directly (with equipment manufacture designation).…”
Section: Discussionmentioning
confidence: 99%
“…Men were about 75% less likely to receive osteoporosis treatment during the hospital stay than women; only 2.2% of men received any osteoporosis treatment, compared to 8.9% of women. In another study of treatment in a Texas hospital, only 27% of men with hip fracture reported receiving treatment 1 year after the fracture, compared with more than two-thirds (71%) of women reporting treatment [19]. Of the men who received treatment, twothirds received calcium and vitamin D (compared to 32% of the treated women), rather than an antiresorptive or bone-forming agent.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Additionally, a lower proportion of men at high risk of fracture are treated than women at high risk [19]. Men also tend to have worse outcomes after fracture than women; they are twice as likely to die after hip fracture than women [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its prevalence across both sexes, osteoporosis does not affect men and women equally [19,30,34]; there are important sex-and gender-based distinctions between men and women that should be acknowledged. The Institute of Medicine recognized the importance of using the term ''sex'' to refer to factors that are primarily biologic in origin and ''gender'' to refer to social and cultural influences based on sex [18].…”
Section: Introductionmentioning
confidence: 99%
“…This distinction is important to understand, as both sex-and gender-based characteristics influence the pathophysiology, diagnosis, prognosis, and treatment of osteoporosis and its sequelae. These sex and gender differences ultimately influence the rates of morbidity and mortality in men who sustain a hip fracture [8,27,30], as men are more likely than women to have osteoporosis that is undiagnosed or undertreated [19,30,34].…”
Section: Introductionmentioning
confidence: 99%